EFFECT OF PHYSICO-CHEMICAL PARAMETERS OF RIVER GANGA (VARANASI) & RIVER SAI (JAUNPUR) ON MORPHOLOGICAL CHANGES IN FISHES (International Journal of Food and Nutritional Sciences, 2023)
We have studied the effect of physico-chemical parameters of river Ganga (Varanasi) & river Sai (Jaunpur) on the Fishes. Qurashi et al has studied the temperature, transparency, pH, BOD, COD and Cl- effected many morphological as well as growth response factors and their habits. It is concluded that these parameters affect the life of fishes. It forms the new species by variations due to adaptation. The results showed that both rivers are affected by pollution from human activities like sewage discharge, agricultural runoff, and industrial waste. These pollutants cause stress in aquatic organisms, especially fishes.